Industry 4.0, global value chains and international business. Issue 3 (18th September 2017) - Strange, Roger; Zucchella, Antonella
Abstract : Purpose: This paper aims to provide an assessment of how the widespread adoption of new digital technologies (i.e. the Internet of things, big data and analytics, robotic systems and additive manufacturing) might affect the location and organisation of activities within global value chains (GVCs). Design/methodology/approach: The approach in this paper is to review various sources about the potential adoption and impact of the new digital technologies (commonly known collectively as Industry 4.0), to contrast these technologies with existing technologies, and to consider how the new technologies might lead to new configurations involving suppliers, firms and customers. Findings: The authors report that the new digital technologies have considerable potential to disrupt how and where activities are located and organised within GVCs), and who captures the value-added within those chains. They also report that Industry 4.0 is still in its infancy, but that its effects are already having an impact upon the nature of competition and corporate strategies in many industries. Social/implications: In particular, the authors draw attention to the potential cyber-risks and implications for the privacy of individuals, and hence, the need for regulation. Originality/value: This is the first published paper to consider the likely separate and joint impacts of the new digital technologies on the practice and theory of international business.